Prevalence of Portuguese Children Exposed to Secondhand Smoke at Home and in the Car - Precioso, José (2019)
Introduction: Children’s exposure to secondhand smoke is a cause of serious health problems and infant morbidity. This is the first nationally representative study conducted in Portugal to describe the prevalence of children exposed to secondhand smoke at home and in the car. Material and Methods: This is a descriptive cross-sectional study with a representative sample of 2396 Portuguese children aged 0 to 9 years old, stratified by age and administrative region NUTS II. Questionnaires were administered between January and September 2016. Results: Results showed that 6.1% of mothers and 11.2% of fathers reported smoking at home. It was found that 4.5% of mothers and 8.3% of fathers reported smoking in the car. Results also showed that 5.4% of children were double exposed to secondhand smoke at home and in the car. Children whose parents were smokers and had a lower level of education were more exposed to secondhand smoke at home. Discussion: Children’s exposure to secondhand smoke has been decreasing in Portugal. Parental smoking and a low educational level were risk factors for children’s exposure to secondhand smoke at home. Conclusion: The main source of children’s exposure to secondhand smoke is parental smoking. As such, it is crucial to implement effective measures to control parental smoking. It is necessary to promote smoking cessation among parents and to ban smoking inside the car.